(untitled) (SAARC Journal of Agriculture, 2020)
The field experiment was carried out at Bangladesh Institute of Nuclear Agriculture, Mymensingh during October 2017 to March 2018, to investigate the effect of different levels of phosphorus and mulches on growth, yield attributes and yield of tomato cv. Roma VF. Two factors: (i) Four levels phosphorus viz., 0, 40, 80 and 120 kg P ha-1 and (ii) four different mulches viz., no mulch (control), water hyacinth, rice straw and banana leaves. The experiment was laid out in two factors randomized complete block design with four replications. The effect of phosphorus levels and mulches on morphological characters: plant height, leaf number plant-1, reproductive characters: number of flower clusters plant-1, flowers plant-1, days to flowering and yield contributing characters: number of fruits plant-1, fruit length, single fruit weight and fruit yield both plant-1 and ha-1 was significant. The highest morphological and reproductive characters, yield contributing characters and fruit yield (71.98 t ha-1) were recorded in 120 kg P ha-1 followed by 80 kg P ha-1 (69.76 t ha-1) with same statistical rank. In contrast, the above morphological, reproductive, yield attributes and fruit yield (47.62 t ha-1) was recorded in control plant where no phosphorus was applied. Application of P @ 80 kg ha-1 was found suitable dose for tomato cultivation. Among the three mulches, water hyacinth had remarkable effect on plant growth and yield attributes which resulting the highest fruit yield (68.35 t ha-1) in tomato. So, we may use water hyacinth mulch with application of 80 kg P for maximizing tomato fruit yield during winter season for silty loam soil. SAARC J. Agri., 18(1): 153-160 (2020)